A Comparative Study of Homoeopathic Decimal Versus Centesimal Potency Medicine in the Treatment of Cervical Spondylosis (Advancements in Homeopathic Research, 2024)
Background: Cervical spondylosis (CS) is a  degenerative condition of the cervical spine found  almost universally in persons over50 years of age. It  has become one of the common problems globally.Methods: An experimental study was conducted on  60 patients diagnosed with cervical spondylosis as per  the inclusion and exclusion criteria. All 60 cases of  cervical spondylosis were randomized into 2 groups  of 30 patients each. One group was prescribed with  Individualized Homoeopathic medicine in decimal  scale potency and the other group was prescribed  with centesimal scale potencies of Individualized  Homoeopathic medicine. The Remedy Response  Evaluation Form was used to assess and interpret  the follow up of the patients. The improvement of  the patients was assessed by the Neck Disability  Index (NDI). Result: Intra-group changes in NDI  score were found statistically significant (P < 0.001,  unpaired t test) group difference though favored  centesimal against decimal. Conclusion: On statistical analysis, the p value was  less than 0.001. Hence there is a significant difference  between post treatment score of centesimal potency  group as compared to decimal potency group.
Keywords: Cervical Spondylosis; Centesimal potency; Decimal potency; Homoeopathy; Neck Disability Index (NDI)